Antifungal activity of Carica papaya fruit extract against Microsporum canis: in vitro and in vivo study - Aljuhani, Salma; Rizwana, Humaira; Aloufi, Abeer S.; Alkahtani, Saad; Albasher, Gadah; Almasoud, Hadeel; Elsayim, Rasha (Frontiers in Microbiology, 2024)
Background: Tinea capitis (T. capitis), commonly known as scalp ringworm, is a fungal infection affecting the scalp and hair. Among the causative agents, Microsporum canis (M. canis) stands out, often transmitted from cats to humans (zoonotic disease). In this study, we investigated the efficacy of Carica papaya (C. papaya), fruit extract against dermatophytes, particularly M. canis, both in vitro and in vivo. Additionally, we aimed to identify the active compounds responsible for suppressing fungal growth and assess the toxicity of C. papaya on human cells. Methodology: It conducted in two parts. First, In Vitro Study include the preparation of C. papaya fruit extract using methanol as the solvent, Phytochemical analysis of the plant extract including Gas chromatography-mass spectrometry (GC-MS) and Fourier-transform infrared spectroscopy (FTIR) was conducted, Cytotoxicity assays were performed using HUH-7 cells, employing the MTT assay (1-(3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyl tetrazolium bromide), Antimicrobial activity against M. canis was evaluated, including: Zone of inhibition (ZI), Minimum inhibitory concentration (MIC), Minimum fungicidal concentration (MFC), M. canis cell alterations were observed using scanning electron microscopy (SEM) and transmission electron microscopy (TEM). Second, In Vivo, Albino Wistar male rats were included. Results: The phytochemical analysis of the methanolic extract from papaya revealed several functional groups, including hydroxyl, ammonia, alkane, carbonate, and alcohol. Additionally, the GC-MS analysis identified 15 compounds, with xanthosine and decanoic acid being the predominant components. The methanolic extract of papaya fruits demonstrated potent antifungal activity: ZI = 37 mm, MIC = 1000 µg/ml, MFC = 1900 µg/ml, MTT results indicated lower cytotoxicity of the fruit extract at concentrations of 20 µg/ml, 50 µg/ml, 100 µg/ml, 150 µg/ml, and 200 µg/ml, The IC50 revealed a significant decrease in cell viability with increasing extract concentration. Notably, papaya extract induced considerable alterations in the morphology of M. canis hyphae and spores. In animal tissue, improvements were observed among the group of rats which treated with Papaya extract. This study highlights the potential of C. papaya fruits as a natural antifungal agent, warranting further exploration for clinical applications.